Relationship of Neighborhood Greenness to Heart Disease in 249 405 US Medicare Beneficiaries. Issue 6 (19th March 2019) - Wang, Kefeng; Lombard, Joanna; Rundek, Tatjana; Dong, Chuanhui; Gutierrez, Carolina Marinovic; Byrne, Margaret M.; Toro, Matthew; Nardi, Maria I.; Kardys, Jack; Yi, Li; Szapocznik, José; Brown, Scott C.
Abstract : Background: Nature exposures may be associated with reduced risk of heart disease. The present study examines the relationship between objective measures of neighborhood greenness (vegetative presence) and 4 heart disease diagnoses (acute myocardial infarction, ischemic heart disease, heart failure, and atrial fibrillation) in a population‐based sample of Medicare beneficiaries. Methods and Results: The sample included 249 405 Medicare beneficiaries aged 65 years and older whose location (ZIP+4) in Miami‐Dade County, Florida, did not change from 2010 to 2011. Analyses examined relationships between greenness, measured by mean block‐level normalized difference vegetation index from satellite imagery, and 4 heart disease diagnoses. Hierarchical regression analyses, in a multilevel framework, assessed the relationship of greenness to each heart disease diagnosis, adjusting successively for individual sociodemographics, neighborhood income, and biological risk factors (diabetes mellitus, hypertension, and hyperlipidemia). Higher greenness was associated with reduced heart disease risk, adjusting for individual sociodemographics and neighborhood income. Compared with the lowest tertile of greenness, the highest tertile of greenness was associated with reduced odds of acute myocardial infarction by 25% (odds ratio, 0.75; 95% CI, 0.63–0.90), ischemic heart disease by 20% (odds ratio, 0.80; 95% CI, 0.77–0.83), heart failure by 16% (odds ratio, 0.84; 95% CI, 0.80–0.88), and atrial fibrillation by 6% (odds ratio, 0.94; 95% CI, 0.87–1.00). Associations were attenuated after adjusting for biological risk factors, suggesting that cardiometabolic risk factors may partly mediate the greenness to heart disease relationships. Conclusions: Neighborhood greenness may be associated with reduced heart disease risk. Strategies to increase area greenness may be a future means of reducing heart disease at the population level. Abstract : See Editorial by Balmes